A scientific way of war antebellum military science, West Point, and the origins of American military thought - Hope, Ian C. (Studies in war, society, and the military, 2015)
While faith in the Enlightenment was waning elsewhere by 1850, at the United States Military Academy at West Point and in the minds of academy graduates serving throughout the country Enlightenment thinking persisted, asserting that war was governable by a grand theory accessible through the study of military science.